Pengelolaan Situs Candi Wasan Pascapemugaran dalam Upaya Meningkatkan Pariwisata Budaya Berbasis Masyarakat - Surya Andari, Putu Ayu; Tara wiguna, I Gusti Ngurah; *, Zuraidah (Humanis; Vol 18 No 1 (2017), 2017)
Wasan temple site is one of the Hindu temple located in Banjar Blahtanah, Batuan Kaler Village, Sukawati District, Gianyar Regency. Wasan temple site has been redeveloped as many as three stages of the year 2009-2011 by Balai Pelestarian Cagar Budaya Bali, NTB, and NTT. Based on the shape of the post-restoration, most likely if Wasan temple can be developed as a tourist attraction. Therefore, the purpose of the study is to examine the potential temple sites and forms management Wasan temple site after the restoration in an attempt to improve community-based cultural tourism. Data collection methods used in this study, observation, library research and interviews as well as methods of data analysis through qualitative analysis and SWOT analysis by applying management theory. Wasan temple site has archaeological potential, among which a monumental temple, Ganesha statues, animal statues, temple building components, and a pool. Moreover, Wasan temple site also has a supporting factor natural resources Kemenuh Butterfly Park and some cultural resources, namely sophisticated temple, Pura Hyang Tiba, Pura Puseh Blahbatuh, egg painting and sculpture. In developing as a tourist attraction, the need for forms of management of planning, organizing, directing, actuating and controlling carried out by pemangku, pengemong and stakeholders. In addition to a management regime in its development also need to consider the strengths, weaknesses, opportunities and threats owned Wasan temple site. In addition, community participation is also very necessary to pass up promotions through tour travel and the internet.
Keywords: management, potential, post-restoration